Biocompatibility enhancement via post-processing of microporous scaffolds made by optical 3D printer - Jeršovaitė, Jurga; Šarachovaitė, Ugnė; Matulaitienė, Ieva; Niaura, Gediminas; Baltriukienė, Daiva; Malinauskas, Mangirdas (Frontiers in Bioengineering and Biotechnology, 2023)
Providing a 3D environment that mimics the native extracellular matrix is becoming increasingly important for various applications such as cell function studies, regenerative medicine, and drug discovery. Among the most important parameters to be considered is the complicated micro-scale geometry and material properties of the scaffold. Therefore, stereolithography based on photopolymerization is highly promising in this field due to its ability to selectively form volumetric structures from liquid resin through polymerization reactions. However, among the vitally essential parameters of scaffold is biocompatibility, which depends mainly on the material, but also exposure conditions and even post-processing. To systematically study this, microporous scaffolds with pore sizes of 0.051727 mm3 corresponding to the porosity of 16,4 % were made with Asiga PICO2 39 UV stereolithography printer of widespread FormLabs Clear and Flex resins. Using them directly for tissue engineering is of limited suitability for cells since after wet chemicalk development the non-negligible amount remaining monomers intertwinned in photopolymerized structures remain significantly toxic to cells. So the aim of this research was to find the best method for the elimination of monomers out of the 3D scaffold using additional UV exposure, for the first time for this purpose applying a Soxhlet extractor and soaking them into different alcohols. Also, through the use of Raman micro-spectroscopy, it was investigated if different post-processing methods affect the degree of conversion (cross-linking) to learn if specifically it affects the biocompatibility of scaffolds. Finally, rat dental pulp-derived mesenchymal stem cells were studied to confirm the increase of biocompatibility on the scaffolds and their ability to support cell differentiation into bone tissue cells.